1997
DOI: 10.1073/pnas.94.8.3848
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RBM in the nuclei of human germ cells is dependent on a critical region of the Y chromosome long arm

Abstract: The association of abnormal spermatogenesis in men with Y chromosome deletions suggests that genes important for spermatogenesis have been removed from these individuals. Recently, genes encoding two putative RNAbinding proteins (RBM and DAZ͞SPGY) have been mapped to two different regions of the human Y chromosome. Both of these genes encode proteins that contain a single RNA recognition motif and a (different) internally repeating sequence. Y-linked RBM homologues are found in all mammalian species. We have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
153
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(161 citation statements)
references
References 38 publications
(39 reference statements)
3
153
0
4
Order By: Relevance
“…Deletions of the AZFb region include at least one functional copy of the RBMY1 gene. A family of PRY genes, essential in the regulation of apoptosis is also found in the AZFb region [53]. Whereas small AZFb deletions have been related to variable testicular phenotypes [54], larger AZFb deletions and those that include genes PRY1/PRY2 seem to cause complete meiotic arrest [34].…”
Section: The Azfb (P5/proximal-p1) Regionmentioning
confidence: 99%
“…Deletions of the AZFb region include at least one functional copy of the RBMY1 gene. A family of PRY genes, essential in the regulation of apoptosis is also found in the AZFb region [53]. Whereas small AZFb deletions have been related to variable testicular phenotypes [54], larger AZFb deletions and those that include genes PRY1/PRY2 seem to cause complete meiotic arrest [34].…”
Section: The Azfb (P5/proximal-p1) Regionmentioning
confidence: 99%
“…Thus, in 1995, it was demonstrated that DAZ mutations (Yq11.23) cause various forms of human male infertility that range from oligospermia to azoospermia 4, 5. In 1997, it was reported that RBMY (Yq11.223) mutations cause azoospermia via meiotic arrest5, 6 and, in 1999, it was shown that USP9Y (Yq11.2) mutations lead to azoospermia that is secondary to hypospermatogenesis 5, 7. The azoospermia factor (AZF) region on the Y chromosome is one of the most intensively studied regions in male infertility 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic causes of azoospermia include chromosomal abnormalities, Y-chromosome microdeletions and several specific gene mutations/deletions affecting genes, such as DAZ, RBMY, USP9Y and SYCP3 [1][2][3][4][5]. As Y-chromosome deletions account for only 16.0% of men with infertility [6], azoospermia in many infertile men may be caused by autosomal gene mutations.…”
Section: Introductionmentioning
confidence: 99%